Optimalisasi Biaya Dan Waktu Terhadap Perencanaan Jalan Dengan Menggunakan Metode Bina Marga 1987 Dengan Berbagai Tebal Indek Perkerasan (Studi Kasus : Pada Ruas Jalan Puruk Cahu - Km 50 - Batas Kota Muara Teweh Kabupaten Barito Utara) - Erlin Meyer (Media Ilmiah Teknik Sipil, 2020)
Pavement planning is good, because in this way the pavement construction is able to carry the load of vehicles passing on it and spread the load to the layers beneath it, including the subgrade, without causing significant damage to the road construction itself. The purpose of this study is to obtain the most efficient alternative pavement thickness index and to obtain the required cost and time. The results showed that the Pavement Thickness Index (ITP) using the Bina Marga Method = 7.48 and the 1993 AASHTO Method = 10.20 had a difference of 2.72. The difference in Pavement Thickness Index (ITP) resulted in the addition of pavement thickness using the 1993 AASHTO Method. The economical Pavement Thickness Index (ITP) was the ITP Bina Marga Method with a construction cost of Rp 12.7 billion, with savings of Rp 3.8 billion. By determining the pavement thickness at the same base layer = 20 cm, it is found that the type of material is Aggregate Class B, CBR is 80% cheaper than cement + CTRB with savings of Rp 913,991,544, - ~ 1 billion. The time required in implementing the Bina Marga Method is more efficient than the 1993 AASHTO Method with a savings of 44 days, this is due to cement work + CTRB = 15 + 29 = 44 days. While Aggregate Class B, CBR 80% only takes 22 days, thus saving 22 is also due to the larger ITP of the 1993 AASHTO Method so that it requires additional thickness of the base layer under Aggregate Class C, CBR 30% of 22 cm thus increasing the duration of the implementation time by 24 days